Implementasi Pendidikan Agama Islam Berbasis Behavioristik di MA An Nawari Bluto Sumenep - Tamimi, Moh (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2023)
There are many ways to make Islamic education efforts for students. Various theories and approaches in education aim to make the educational process a success, one of which is behavioral theory and approaches. This research wants to prove how behavior theory is implemented at MA An Nawari. The research method used in this research is field qualitative with a case study approach. This research concludes that the environment built in the educational process at MA An Nawari is Islamic values ​​with spiritual, moral, cleanliness, discipline and courage (self-confidence). In its implementation, the five Islamic values ​​are carried out well using theory and behavioral approaches.